Funcionalidade, lombalgia e cervicalgia em idosos institucionalizados e fatores associados - Souza, Wellington Cesar de (2018)
Aging is associated with chronic degenerative diseases of the spine, which occur with low back pain and/or neck pain. Disability secondary to these morbidities restricts the elderly's activities and causes dependency, which is associated with institutionalization, and demands care and costs. The objective of the dissertation is to verify the disability secondary to low back pain and neck pain, contextualizing it with the available literature, and aim the publications of the knowledge in two productions: Functional incapacity secondary to low back pain in institutionalized elderly, and associated factors and Functional incapacity secondary to neck pain in institutionalized elderly and associated factors. This is a cross-sectional study, with elderly individuals aged 60 years and over, living in long-term care facilities for the elderly in the municipalities of Passo Fundo, Carazinho and Bento Gonçalves, state of Rio Grande do Sul, RS. The study was approved by the Ethics Committee of the University of Passo Fundo (UPF), Rio Grande do Sul, RS, Brazil (Opinion nº 2097278). The elderly were interviewed with structured questionnaire containing demographic, clinical variables and the evaluation scales Oswestry Disability Index and Neck Disability Index. The sample consisted of 116 elderly individuals, 58,6% presented low back pain, and of these, 61,7% of the cases presented minimal or moderate disability, and 11,8% presented severe disability and disability. The prevalence of neck pain was 39,7%, 67,4% had minimal or moderate disability, and 6,5% had severe disability or invalidity. Low back pain was associated (p <0.05) with neck pain, rheumatism, chronic pain in the last 6 months, Geriatric Depression Scale suggestive of depression, osteoporosis and polypharmacy. However, in the final model the Adjusted Prevalence Ratio (APR) for neck pain (APR = 0,86, CI 0,76 -0,98) and Geriatric Depression Scale suggestive of depression (APR = 0,87, CI 0,77-0,98). Neck pain presented an association (p <0.05) with low back pain, rheumatism and chronic pain in the last 6 months, although the RPA showed significance for low back pain (APR = 0,855, CI 0,768 – 0,952) and fecal incontinence (APR = 0,829, 0,697-0,986 ), without confirmation of significance for rheumatism and chronic pain in the last 6 months. There was a high prevalence of low back pain in institutionalized elderly, and the association with neck pain and Geriatric Depression Scale suggestive of depression. The prevalence of cervicalgia found was high, and the association with low back pain and fecal incontinence was found. The Oswestry Disability Index and Neck Disability Index disability indexes were consistent for use in the elderly population without cognitive decline.